Annotazioni Critiche su Aquila e Priscilla, il Titulius Priscae e le Catacombe di Priscilla a Roma - Ramelli, Ilaria (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2000)
The article proposes an analysis of the tradition concerning Aquila and Priscilla; the titulus Priscae in Rome is probably connected not with Aquila's wife, but with the later Virgin and Martyr St. Frisca. We don't know whether the Aquila and the Priscilla who were buried in the catacombs of Priscilla can be identified with St. Paul's friends, but it is sure that these catacombs were possessed —at a very early date— by the Acilii Glabriones. They contain inscriptions from the llnd century AD onward, but perhaps there were Christian members of the family already in the Ist century: one of the Acilii Glabriones was a Román senator who was put to death during Domitian's persecution; and it is highiy probable that he was a Christian. L'étude analyse en premier lieu la tradition sur Aquila ef Priscille. Probablement le titulus Priscae est lié non avec la femme d'Aquila, mais avec la plus tarde Vierge et l\/lartyr Pasque. Nous ne savons pas si les Aquila et Priscilla ensevelis dans le cimetiére de Priscilla sont identifiables avec les amis de saint Paul, mais il est bien sur que le cimetiére était propriété des Acilii Glabriones des une tres haute antiquité. Dans le méme cimetiére ont efe découvertes plusleurs inscriptions du líeme siécle apr. J.-C, peut-étre ainsi du ler. Á la fin du ler siécle apr. J.-C. un Acilius Glabrio, senateur romain, fut condamné a mort par Domitien, et tres probablement il était chrétien.